The archaeology and meaning of the boat-shaped stone markers in Vuhus Island, Batanes Province, Northern Philippines - Valientes, Edwin A. (Hukay, 2019)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/6862/5950